Pelatihan Teknologi Internet of Things Dan Mobile untuk Meningkatkan Kompetensi bagi Guru pada SMK Sulthan Muazzam Syah Pekanbaru - Imardi, Syahrul; Tashid, Tashid; Yenni, Helda; Efendi, Yoyon; Muzawi, Rometdo (UIR Press, 2024)
The weak ability of teachers in the field of network expertise, especially technology-based, also has an impact on the Competency Test (UKK) of school students. The implementation of Internet of Things (IoT) and Mobile Technology training to improve teacher competence at SMK Sulthan Muazzam Syah (SMS) was attended by 18 teachers from various schools. In addition to SMS SMK teachers, there are also SMK Perbankan teachers, SMK Plus Terpadu, SMK Ekatama, SMKS Global, SMK MM Masmur, SMK Taruna Masmur and SMK Pharmacy Ekasari Pekanbaru in the field of Computer Network Engineering (TKJ). This activity lasts for 3 days starting from the delivery of material followed by practicum. For evaluation using pre-test and post-test techniques. The material is delivered starting from the introduction of the Internet of Things (IoT), IOT practicum, introduction to mobile technology, mobile technology practicum and evaluation of devotion in the form of handover of minutes of handover. The result is an increase in knowledge and skills to be applied in schools to students. In order to improve the quality of graduates and schools in the fields of IOT and mobile.